2021
DOI: 10.1002/jcpy.1232
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Indirect Appeals in Peer‐to‐Peer Fundraising: Why “S/He” Can Raise More Money for Me Than “I” Can For Myself

Abstract: The proliferation of peer-to-peer fundraising platforms (e.g., GoFundMe, Rally, Fundly) poses conceptual and substantive challenges for behavior scientists and fundraisers. This article explores how fundraisers should craft their appeals to maximize their chance of success. Four fieldand laboratory-studies find that direct appeals (i.e., narratives written in the first person by the intended recipient) raise less money than otherwiseidentical indirect appeals (i.e., narratives written in the third person, seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The wealth of advertising literature supported the positive effects of indirect appeal to enhance the credibility of product either through TPOs (Chen and Xie, 2005; Dean and Biswas, 2001; Yuan et al , 2020) or endorsers such as celebrities, athletes or social media influencers (Bauer et al , 2022; Carrillat and d’Astous, 2014; Kapitan and Silvera, 2016; Spry et al , 2011; Wohlfeil et al , 2019). In recent years, scholars show that indirect appeal can be effective in fundraising by providing informational social influence (Sepehri et al , 2021). Despite valuable insights, we still do not know how long the effect of indirect appeal lasts (Hill et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The wealth of advertising literature supported the positive effects of indirect appeal to enhance the credibility of product either through TPOs (Chen and Xie, 2005; Dean and Biswas, 2001; Yuan et al , 2020) or endorsers such as celebrities, athletes or social media influencers (Bauer et al , 2022; Carrillat and d’Astous, 2014; Kapitan and Silvera, 2016; Spry et al , 2011; Wohlfeil et al , 2019). In recent years, scholars show that indirect appeal can be effective in fundraising by providing informational social influence (Sepehri et al , 2021). Despite valuable insights, we still do not know how long the effect of indirect appeal lasts (Hill et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Addressing this gap, we theorize that indirect appeal by a TPO to deliver an FPRC's commercial ad influences the path from duality to consumer attitude toward the ad by mitigating greed perception. For instance, Sepehri et al (2021) show that charitable appeals framed in an indirect fashion (e.g. written in a third-person voice, seemingly by a third party on behalf of someone else) are more effective than direct appeal (e.g.…”
Section: Indirect Appeal and Greedmentioning
confidence: 99%
See 1 more Smart Citation
“…As already noted, one was a one-day campaign, which eliminated the possibility of studying dynamics. Another (Sepehri et al 2021) addressed the effectiveness of direct versus indirect appeals, a topic that is not covered in this study. We are unaware of studies of the dynamics of charitable campaigns, which may differ from the dynamics of reward-based campaigns because the latter solicit investments in a tangible reward.…”
Section: Literature On Response To Online Campaignsmentioning
confidence: 99%
“…Responses to online crowdfunding campaigns have been studied from various angles. For instance, Herzenstein, Sonenshein, and Dholakia (2011) investigated the effectiveness of infusing identity claims on campaigns; Galak, Small, and Stephen (2011) demonstrated the positive relationship between donor-fundraiser similarity; and Sepehri et al (2021) showed that indirect appeals are more effective than direct appeals. However, an extensive literature review indicates that the pattern of funding raised from donors follows three phases (see the review in Kim et al 2020).…”
Section: The Three-phase Processmentioning
confidence: 99%